Physiological Responses of Goldfish and Naked Mole-Rats to Chronic Hypoxia: Membrane, Mitochondrial and Molecular Mechanisms for Metabolic Suppression - Farhat, Elie (Université d'Ottawa / University of Ottawa, 2021)
Chronic hypoxia is a state of oxygen limitation that is common in many aquatic and terrestrial environments. Metabolic suppression is an essential strategy that is used by hypoxia-tolerant champions such as goldfish and naked mole-rats to cope with prolonged low oxygen. This thesis examines the physiological processes used by goldfish and naked mole-rats to survive in low oxygen environments. It proposes a novel mechanism - the remodeling of membrane lipids - to reduce ATP use and production. Temperature (homeoviscous adaptation), diet (natural doping in migrant birds) and body mass (membrane pacemaker of metabolism) have an impact on the lipid composition of membranes that, in turn, modulates metabolism. In chapters 2 and 3 of this thesis, I demonstrate that vertebrate champions of hypoxia tolerance undergo extensive changes in membrane lipid composition upon in vivo exposure to low oxygen. These changes and those observed in hibernating mammals can promote the downregulation of Na⁺/K⁺-ATPase (major ATP consumers), mitochondrial respiration capacity [OXPHOS (phosphorylating conditions), proton leak (non-phosphorylating conditions), cytochrome c oxidase], and energy metabolism (β-oxidation and glycolysis) as discussed in chapters 3 and 4. A common membrane signal regulating the joint inhibition of ion pumps and channels could be an exquisite way to preserve the balance between ATP supply and demand in hypometabolic states. In chapter 5, I show that the reduction in ATP turnover is also orchestrated by mechanisms that involve post-translational and post-transcriptional modifications and epigenetic changes. Membrane remodeling, together with these more traditional molecular mechanisms, could work in concert to cause metabolic suppression.
Keywords: Hypoxia; Membrane lipids; Metabolic suppression; Cholesterol; Phospholipids; Na⁺/K⁺-ATPase; Glycolysis; Beta-oxidation; Mitochondrial respiration; Transcription silencing; mRNA; Membrane restructuring